Geotechnical Evaluation of Baktiari Hill Kurdistan District/Iraq - Al-Khateeb, Azhar A. G.; Capigian, Arsen O. (Sulaimani Journal for Pure and Applied Sciences, 2013)
A comprehensive geotechnical study is carried out in Northeastern part of Iraq for a site in Sulaimaniya Governorate which is located about (4) km. from city center, a site where a grand hotel were constructed later on. The site is a longitudinal hill representing a double plunging anticline, which itself is the southeastern plunge of Pera-Magroon anticline, regionally the area is highly affected by tectonic movements which led to folding, faulting, jointing, shearing …etc. The site is evaluated by studying the core of (9) boreholes with (200) m length through three engineering parameters: Rock Quality Designation (RQD), Fissuration Factor (CFactor) and Number of Fractures per meter (F/m) besides two laboratory parameters: Unconfined Compressive Strength (c) and Porosity (Pₒ). Each borehole is divided into different geotechnical horizons according to the similarity of engineering parameter values, weathering degree, color, bedding, etc. Weighted average of the five above mentioned parameters are calculated for these horizons where each parameter classify the rock mass into five ranks from very weak to excellent with rank values from one to five; these values are adopted to get final evaluation of the boreholes. Subsurface correlation charts are drawn using Rockworks/15 program depending upon the evaluation of each horizon which is gained by matching rank values of each parameter to get the final rank values of it from weak to excellent which is used for the first time by the authors.
Keywords: Geotechnical horizon; rank value; rock mass rating; numerical value